Implementing resources to support the diagnosis and management of Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME) in primary care: A qualitative study. Issue 1 (December 2016) - Bayliss, Kerin; Riste, Lisa; Band, Rebecca; Peters, Sarah; Wearden, Alison; Lovell, Karina; Fisher, Louise; Chew-Graham, Carolyn
Abstract Background Previous research has highlighted that many GPs lack the confidence and knowledge to diagnose and manage people with CFS/ME. Following the development of an online training module for GPs, and an information pack and DVD for patients, this study explored the extent to which these resources can be implemented in routine primary care. Methods Semi structured qualitative interviews were completed with patients and GPs across North West England. All interviews were transcribed and analysed using open exploratory thematic coding. Following this thematic analysis, the authors conducted a further theory-driven analysis of the data guided by Normalisation Process Theory. Results When used in line with advice from the research team, the information resource and training were perceived as beneficial to both patients and GPs in the diagnosis and management of CFS/ME. However, 47 % of patients in this study did not receive the information pack from their GP. When the information pack was used, it was often incomplete, sent in the post, and GPs did not work with patients to discuss the materials. Only13 out of 21 practices completed the training module due to time pressures and the low priority placed on low prevalence, contentious, hard to manage conditions. When the module was completed, many GPs stated that it was not feasible to retain the key messages as they saw so few patients with the condition. Due to the complexity of the condition, GPs also believed that the diagnosis and management of CFS/ME should take place in a specialist care setting. Conclusion While barriers to the implementation of training and resources for CFS/ME remain, there is a need to support CFS/ME patients to access reliable, evidence based information outside primary care. Our findings suggest that future research should develop an online resource for patients to support self-management.